A Modified Bat Algorithm for Power Loss Reduction in Electrical Distribution System - Djossou Adeyemi Amon (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Losses on Electric Distribution System lines represent a major challenge for electric distribution companies since those losses refer to the amount of electricity injected into the distribution grids that are not paid by users. Network Optimization by system reconfiguration is one of the solutions among many others used to solve this problem. In this paper a modified version of new Meta Heuristic algorithm based on Bat behavior is proposed to find the best system configuration with a low loss rate, we present two different approaches: reduction of search space and introduction of sigmoid function to fit the algorithm to the problem. The main advantages of the proposed methodology are: easy implementation and less computational efforts to find an optimal solution. To demonstrate its efficiency the proposed scheme is tested on 33 Bus distribution system and the results show loss reduction rate of 33%. DOI:  http://dx.doi.org/10.11591/telkomnika.v14i1.7629